Degradation of phenol in wastewater by cathodic microarc plasma electrolysis. Issue 8 (3rd April 2019) - Zhang, Yifan; Liu, Guijun; Wang, Ying; Shen, Chanchan; Zhang, Zhanbin; Shang, Hongzhong; Xue, Wenbin
ABSTRACT: In this paper, the cathodic microarc plasma electrolysis (CMPE) was tentatively performed to degrade the phenol in aqueous solution by vapor-gaseous envelope discharge around the Ti cathode. Degradation efficiency of phenol was measured and the intermediate products were evaluated. The suspended particles in solution were analyzed and the decomposition mechanism of phenol in the process of cathodic microarc plasma degradation was discussed. The instantaneous current efficiency reached a peak value firstly and then decreased with the discharge time. In the cathodic plasma region, the Cl substituted the hydrogen on benzene ring in the initial time, which was replaced by a hydroxyl immediately, then the polyhydroxy phenol was easily decomposed. In addition, optical emission spectroscopy was carried out to characterize the plasma features during the CMPE process. The temperature of electron around the microarc discharge envelope reached about 4000 K; thus the phenol was partly carbonized to become graphite particles. CMPE is a promising approach to degrade quickly the phenol in wastewater.